Impression Management and Organizational Performance in the Fast Food and Restaurant Sector in Nigeria - Ginah, Ginah O.; Akpotu, Christopher (Archives of Business Research, 2016)
This study examined impression management practices in work organization and their link with organizational performance in the fast food sector. Impression management construct was examined with its adapted dimensions and it was also the case with organizational performance. The structured survey instrument was used to generate data from the sampled managers. The analysis of data shows a positive but moderate link between impression management and performance of firms measured by market size and profitability. It was also found that up to 34.5% of variability in performance is predicted by impression management practices and information balancing and imaging are two components of impression management with highest weights = 0.442 and = 0.318 respectively on the performance of firms in the sector. It was concluded that impression management practices are considered strategic actions that influence performance of organization in terms of market share and profitability therefore it is recommended that operators in the sector should ensure information balancing and positioning as a means of ensuring continued customer patronage through impression created.